Micro‐Seismic Monitoring of a Shear Fault Within a Floating Ice Plate. Issue 10 (25th October 2019) - Lachaud, Cédric; Marsan, David; Montagnat, Maurine; Weiss, Jérôme; Moreau, Ludovic; Gimbert, Florent
Abstract: The deformation of a circular fault in a thin floating ice plate imposed by a slow rotational displacement is investigated. Temporal changes in shear strength, as a proxy for the resistance of the fault as a whole, are monitored by the torque required to impose a constant displacement rate. Micro‐seismic monitoring is used to study the relationship between fault average resistance (torque) and micro‐ruptures. The size distribution of ruptures follows a power‐law scaling characterized by an unusually high exponent ( b ≃3), characteristic of a deformation driven by small ruptures. In strong contrast to the typical brittle dynamics of crustal faults, an 'apparently aseismic' deformation regime is observed in which small undetected seismic ruptures, below the detection level of the monitoring system, control the slip budget. Most (≃71%) of the detected ruptures are organized in bursts with highly similar waveforms, suggesting that these ruptures are only a passive by‐product of apparently aseismic slip events. The seismic signature of this deformation regime has strong similarities with crustal faulting in settings characterized by high temperature and with non‐volcanic tremors. Key Points: A micro‐seismic monitoring of a fault is setup to monitor its deformation Small undetected fractures control the slip and energy budgets of the fault Fractures are mostly a by‐product of the imposed slip, similarly to swarm‐seismicity